Demographics as Variable in Assessing the Teaching Competence of Teachers in Catholic Schools - Jorilla, Chona D.; Bual, Joel M. (Philippine Social Science Journal, 2020)
Competent and quality teachers are the principal key of an excellent educational system, for they contribute to the integral formation of the learners. Their unique role in the teaching-learning process enables these children to maximize their potentials in becoming active and critical thinkers. Through this professional endeavor, they become stewards of knowledge not only for learners but also for the building and growth of the nation. Thus, for teachers to perform this mission, they must show high regard for professional standards and competence. However, most Catholic schools nowadays are confronted with the challenges of teaching competence due to the gradual migration of qualified educators to public institutions considering the demands of high remuneration and K-12 educational reform. In this sense, they resort to hiring new and unqualified teachers who compromise the continuity of quality Catholic teaching and learning. Hence, the paper assessed the level of teaching competence of Diocesan Catholic schools in Antique in the light of content knowledge and pedagogy, learning environment, diversity of learners, curriculum and planning, assessment and reporting, community linkages and professional engagement, and personal growth and professional development domains of Philippine Professional Standards for Teachers (PPST). Likewise, it sought to establish the relationship between teaching competence and their age, sex, employment status, and professional status.